2019
DOI: 10.1002/rcm.8378
|View full text |Cite
|
Sign up to set email alerts
|

Strontium isotope ratios of human hair from the United States: Patterns and aberrations

Abstract: Rationale Strontium isotope ratios (87Sr/86Sr) of hair may be a valuable tool to estimate human provenance. However, the systematics and mechanisms controlling spatial variation in 87Sr/86Sr of modern human hair remain unclear. Here, we measure 87Sr/86Sr of hair specimens from across the USA to assess the presence of geospatial relationships. Methods Ninety‐eight human hair specimens were collected from salon/barbershop floors in 48 municipalities throughout the conterminous USA. [Sr] and 87Sr/86Sr ratios were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 72 publications
0
13
0
Order By: Relevance
“…However, because of the complexity of the modern supermarket diet, it is almost impossible to compile the 87 Sr/ 86 Sr ranges of local foods from all traveled locations. As previous studies have shown that the hair samples usually have the same 87 Sr/ 86 Sr as the local tap water (Tipple et al, 2019;Ammer et al, 2020), we chose the 87 Sr/ 86 Sr ratios of the tap water samples in the FAD (Chartrand and St-Jean, 2015) and the river or tap water samples in the literature (Voerkelius et al, 2010;Chesson et al, 2012;Bataille et al, 2020b) to estimate the range of hair 87 Sr/ 86 Sr for the studied individual.…”
Section: Estimate Isotope Ranges From the Forensic Attribution Database And The Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…However, because of the complexity of the modern supermarket diet, it is almost impossible to compile the 87 Sr/ 86 Sr ranges of local foods from all traveled locations. As previous studies have shown that the hair samples usually have the same 87 Sr/ 86 Sr as the local tap water (Tipple et al, 2019;Ammer et al, 2020), we chose the 87 Sr/ 86 Sr ratios of the tap water samples in the FAD (Chartrand and St-Jean, 2015) and the river or tap water samples in the literature (Voerkelius et al, 2010;Chesson et al, 2012;Bataille et al, 2020b) to estimate the range of hair 87 Sr/ 86 Sr for the studied individual.…”
Section: Estimate Isotope Ranges From the Forensic Attribution Database And The Literaturementioning
confidence: 99%
“…Previous studies demonstrated that the 87 Sr/ 86 Sr ratios in hair are strongly related to the 87 Sr/ 86 Sr ratio of local tap water (Tipple et al, 2018(Tipple et al, , 2019Ammer et al, 2020). If the hair of the volunteer recorded the 87 Sr/ 86 Sr ratios of tap water at traveled locations by drinking the tap water and incorporating its 87 Sr/ 86 Sr ratio into hair through the bloodstream like the light stable isotope systems, we would expect large 87 Sr/ 86 Sr variations throughout the predicted profile shown in Figure 5.…”
Section: Comparing the Predicted Isotopic Profile And The Measured Isotopic Values Of Strontiummentioning
confidence: 99%
See 1 more Smart Citation
“…Three main sources are considered to contribute to the 87 Sr/ 86 Sr ratios in human hair: exogenous, drinking water, and diet. Despite the fact that several studies have reported potential exogenous signatures embedded in human hair, most likely influenced by bathing in local tap water and from local dust [33][34][35][36], it is argued in this study, that the "contamination" would be of local origin and therefore not significantly offset the results in terms of potential provenance information. As previously mentioned, Mexico is known to be one of the highest bottled water consumers in the world.…”
Section: Discussionmentioning
confidence: 60%
“…Researchers have argued that the 87 Sr/ 86 Sr ratios in human hair may be skewed due to exogenous signatures embedded in human hair, such as bathing water and dust [33][34][35][36]. Any "contamination" is in fact local and therefore will not significantly influence the goal of characterizing the bioavailable Sr of a region.…”
Section: Introductionmentioning
confidence: 99%